Tropical Fruits, (2nd Edition): Volume 1 - Paull, Robert E (CABI, 2014)
The monoaxial banana, pineapple and papaya and polyaxial mango are the most well-known tropical fruits worldwide. Avocado is better known for production in subtropical areas, but considerably more production occurs in the tropical zone. Banana, pineapple and avocado are extensively grown by large companies. Banana, along with plantain, is the largest fruit crop in the tropics, with only a small fraction entering international commerce. Many other tropical fruits, already well known in the tropics, are now appearing in larger temperate city markets. The ﬁ rst edition of this book was started by Dr Henry Nakasone after he retired from the University of Hawaii at Manoa in 1981. His work on the book was prolonged because of his extensive volunteer and consulting activities from his retirement to 6 months before his death in 1995. The extensive research carried out by Henry in preparing some draft chapters laid the foundation for the 1998 ﬁ rst edition. Henry understood the need for a book that melded equally the genetics, physiology and cultural practices with postharvest handling of each fruit crop as an interrelated whole.